Neuropeptide W regulates proliferation and differentiation of ATDC5: Possible involvement of GPR7 activation, PKA and PKC‐dependent signalling cascades. Issue 3 (4th January 2019) - Wang, RiKang; Zheng, Chaojun; Jiang, Wenyu; Xie, Xinshu; Liao, Rifang; Zhou, Guangqian
Abstract: Various neuropeptides related to the energy equilibrium affect bone growth in humans and animals. Neuropeptides W (NPW) are identical in the internal ligands of the two G‐protein receptors (GPRs) included in subtypes 7 and 8. Neuropeptides W inhibits proliferation in the cultivated rat calvarial osteoblast‐like (ROB) cells. This study examines the expression of NPW and GPR7 in murine chondrocyte and their function. An immunohistochemical analysis showed that NPW and GPR7 were expressed in the proliferative chondrocytes of the growth plates in the hind limbs of mice. The NPW mRNA quickly elevated in the early differentiation (7‐14 days) of ATDC5 cells, while NPW and GPR7 mRNA were reduced during the late stage (14‐21 days) of differentiation. Neuropeptide W‐23 (NPW‐23) promoted the proliferation of ATDC5 cells, which was attenuated by inhibiting the GPR7, protein kinase A (PKA), protein kinase C (PKC) and ERK1/2 pathways. Neuropeptide W‐23 enhanced the early cell differentiation, as evaluated by collagen type II and the aggrecan gene expression, which was unaffected by inhibiting the ERK1/2 pathway, but significantly decreased by inhibiting the PKA, PKC and p38 MAPK pathways. In contrast, NPW‐23 was not involved in the terminal differentiation of the chondrocytes, as evaluated by the mineralization of the chondrocytes and the activity of the alkaline phosphatase. Neuropeptides W stimulated the PKA, PKC, p38 MAPK and ERK1/2 activities in a dose‐ and time‐dependent manner in the ATDC5 cells. These results show that NPW promotes the proliferation and early differentiation of murine chondrocyte via GPR7 activation, as well as PKA and PKC‐dependent signalling cascades, which may be involved in endochondral bone formation.